Systematics of Guajirolus ektrapeloglossa Flowers 1985 (Ephemeroptera: Baetidae) - Kluge, Nikita J. (Zootaxa, 2019)
Larva, subimago, imago and eggs of Guajirolus ektrapeloglossa Flowers 1985 are described based on reared males and females from the type locality in Panama and a reared female from Peru. Structure and development of male genitals testify that the Neotropical taxon Guajirolus/g1 (incl. Chane) does not belong to Labiobaetini Kluge & Novikova 2016 and, therefore, is not related to the Afrotropical genus Pseudopannota Waltz & McCafferty 1987. At the same time, larvae of Guajirolus have striking similarity with that of Pseudopannota. The existent descriptions of Guajirolus nanus Lugo-Ortiz & McCafferty 1995, G. queremba Nieto 2003 and G. flowersi Thomas & Dominique (in Thomas, Dominique & Orth) 2005 do not contain characters allowing to distinguish them from G. ektrapeloglossa. Thus, new synonymy is proposed: G. ektrapeloglossa (= G. nanus syn. n.; G. queremba syn. n.; G. flowersi syn. n.). Among the characters described as species-specific for Guajirolus rondoni Salles 2007, only the shape of labial palps allows to distinguish it from G. ektrapeloglossa.